2016
DOI: 10.1002/dta.1945
|View full text |Cite
|
Sign up to set email alerts
|

Test purchase, synthesis and characterization of 3‐fluorophenmetrazine (3‐FPM) and differentiation from its ortho‐ and para‐substituted isomers

Abstract: The knowledge captured in patent and scientific research literature stimulates new ideas and fosters new drug development efforts. Manufacturers and entrepreneurs dedicated to the sale of ‘research chemicals’ and/or new psychoactive substances (NPS) also make use of access to information to identify, prepare, and launch a range of new substances. One of the most recent compounds to appear on the NPS market is the phenmetrazine analog 3‐fluorophenmetrazine (3‐FPM) which represents one of many phenylmorpholines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 25 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…The human urine sample presented with an equal amount of phenmetrazine and 3-FPM. The impurities from the positional isomers 2-FPM and 4-FPM, was not tested in present study, but was previously found not to be present in testpurchased 3-FPM powders from online vendors [2].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The human urine sample presented with an equal amount of phenmetrazine and 3-FPM. The impurities from the positional isomers 2-FPM and 4-FPM, was not tested in present study, but was previously found not to be present in testpurchased 3-FPM powders from online vendors [2].…”
Section: Resultsmentioning
confidence: 91%
“…The main MBPs of 3-FPM in wastewater were the carboxy metabolite (8), while in P. putida TSB growth cultures it was the N-oxide (1). The main excretion product in rat was the aryl hydroxylated metabolites (2), and in human urine it was the unchanged drug, in line with previous studies showing a similar drug/metabolite pattern after administration of phenmetrazine to rats and humans, respectively [15]. Urinary excretion is the main excretion pathway of phenmetrazine [3], as 3-FPM is an analogue to phenmetrazine, urinary excretion is assumed to be the main route of excretion for 3-FPM making the NPS suitable for evaluation by WBE.…”
Section: Proposed Metabolic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…3-FPM, also known as PAL-593, first became available in 2014, and is a fluorinated version of phenmetrazine (figure 2A), an abused drug from the 1960s used as an appetite suppressant 6. 3-FPM acts as a norepinephine dopamine releasing agent and hence has stimulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…3-FPM is one of many phenylmorpholines designed to treat obesity or ameliorate drug dependence [4]. It is suggested that it has properties similar to amphetamines associated with monoamine release [5]. There are many unofficial reports of effects available on the internet, supplied by users.…”
Section: Introductionmentioning
confidence: 99%